Establishment of Functional and Molecular Ultrasound for Breast Cancer Xenograft Imaging - Bzyl, J. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
The present work was originally published in European Radiology and as a PhD thesis at the RWTH Aachen University and was conducted at the Institute for Experimental Molecular Imaging at the RWTH Aachen University.Citation Format:• Bzyl J. Establishment of Functional and Molecular Ultrasound for Breast Cancer Xenograft Imaging. Fortschr Röntgenstr 2014; 186: 377 – 379
Keywords: breast; ultrasound; angiogenesis; animal investigations